An empirical investigation of the impact of redistribution on leisure consumption in OECD countries. (1st January 2014) - Guccio, Calogero; Mignosa, Anna
This paper provides an empirical investigation of the relationship between welfare expenditures and preferences for leisure consumption. The analysis is based on an unbalanced panel of 21 OECD countries and uses several fixed effects estimators to take into account cultural and social differences across countries. Contrary to previous studies, the data used here include public as well as private expenditure. This allows determining whether there are differences according to the public or private character of the expenditure and examining the interaction between household consumption and government intervention. The impact of economic, socio-demographic and political variables on leisure consumption is investigated. Our results show that redistributive social programmes and leisure consumption are complementary and provide evidence of different patterns of behaviour between government and private leisure expenditure. Furthermore, our findings offer some support to a recent theoretical conjecture suggesting that observed international differences in labour supply and welfare expenditure can be due to cultural and social differences across countries and preferences for leisure consumption.